2010
DOI: 10.1021/jp107930a
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical Study of α-Aliphatic Amino Acid Films in the Vacuum Ultraviolet Region

Abstract: A series of natural circular dichroism (CD) and absorption spectra for films of α-aliphatic amino acids--such as alanine, aminobutyric acid, norvaline, norleucine, valine, leucine, and isoleucine--in the vacuum ultraviolet (VUV) region were observed with the absolute values of optical constants at the undulator-based CD beamline TERAS BL5. Preliminary predictions of some CD spectra were also performed, based on quantum-chemical calculations using the crystal structure. Although the absorption spectra show simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 48 publications
(145 reference statements)
4
32
0
Order By: Relevance
“…The origin of the main peak in the CD spectrum of amorphous solids at around 185 nm, resulting in a smaller signal at around 190 nm in the anisotropy spectrum, remains unclear. It has, however, been suggested that this represents the π → π* transition …”
Section: Resultsmentioning
confidence: 99%
“…The origin of the main peak in the CD spectrum of amorphous solids at around 185 nm, resulting in a smaller signal at around 190 nm in the anisotropy spectrum, remains unclear. It has, however, been suggested that this represents the π → π* transition …”
Section: Resultsmentioning
confidence: 99%
“…Within a bottom-up approach of biomolecular complexity, the study of gas-phase, isolated, elementary bricks of life [108] such as amino acids aims at shedding light on their molecular and electronic structures, chemical reactivity, and chiroptical properties. In the next section, we will focus onto alanine (Ala), the simplest chiral proteogenic amino acid, for which not much is known in terms of VUV chiroptics, except for a gas-phase study that reported on the total ion yield providing CD upper values [109], as well as another study on thin films [110]. We will show how PECD of alanine may be of interest in terms of structure (conformational analysis) and, most of all, we will stress a possible link between PECD and the origin of life's homochirality.…”
Section: Case Of Amino Acids Ala and Pro: Possible Implications For Tmentioning
confidence: 99%
“…These measurements required the preparation of amino acids as amorphous thin solid films to avoid the strong VUV absorption of commonly used solvents. Moreover, the isotropic solid form of chiral biomolecules is proposed to better reflect their natural environment in interstellar ices [18,19,20]. Thanks to this progress, CD spectra of meteoritic α-H amino acids and α-methyl amino acids have been recorded [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%